Pengaruh Kompensasi dan Kepuasan Kerja terhadap Kinerja Guru di Sekolah Menengah Atas se-Kabupaten Teluk Bintuni Papua Barat Perspektif Syariah - Hikmah, Nuril; Fathoni, Mohammad; ferdi Andri Asmawan, Yudhi; Ansori, Ansori; Aminudin Al Kusuma Putra, Saiful (Institut Agama Islam YPBWI Surabaya, 2024)
The aim of this research is to examine the effect of compensation and Job Satisfaction on the performance of high school teachers at the High School Education Service in Teluk Bintuni Regency, West Papua, a total of 301 people and 99 teachers who participated as samples in this research. To test the hypothesis in this research using path analysis. After testing the level of validity and regression, it is proven that: Compensation has a positive effect on employee performance. This is shown in the results of simple linear regression which has a calculated t value of 2.142 which is greater than the t table of 1.991. Compensation has a positive influence on employee performance which is mediated by job satisfaction. This is shown in the results of simple linear regression which has a calculated t value of 6,595 which is greater than the t table of 1,991 and a mediation coefficient of 0.154. So it can be concluded that compensation has a positive effect on employee performance which is mediated by job satisfaction. The sharia perspective is defined as God's goal in establishing laws for all of His servants. The essence of the sharia perspective is to realize goodness by avoiding evil or attracting benefits.